Room temperature line parameters of the self- and air-broadened fundamental vibrational transition of carbon monoxide: experimental results and calculations. (July 2019) - Predoi-Cross, A; Islam, N; Smith, M A H; Devi, V M; Ivanov, S; Buzykin, O; Thibault, F
Abstract: We have analyzed 10 room temperature spectra of the fundamental band of CO and CO-air using the Voigt, speed-dependent Voigt, speed-dependent Rautian line shape models. Line positions, intensities, air- and self-broadening coefficients, pressure induced air- and self-shift coefficients, and line-mixing parameters have been retrieved. The CO- and N2 -broadened carbon monoxide half width coefficients have been calculated using a potential energy surface based on Tipping-Herman intermolecular interaction potential and taking the electrostatic interactions into account.